Characterisation and surface plasmon resonance of omeprazole loaded silver nanoparticles - Patani , Bernard O.; Jackson, Tenderwealth C.; Otafu, Covenant O.; Etim, Martha E.; Etim, Yakndara J.; Ntia , Grace U.; Essien, Ekema S. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2024)
Background: Green synthesis approach of nanoparticles formulation utilizes simple, cost-effective, and eco-friendly techniques with no toxic by-products. This method was adopted in this study. Aim: the main objective of this research was to develop and characterise omeprazole loaded silver nanoparticles using standard techniques Methods: Curcuma longa aqueous extract was used as both the reducing and stabilizing agent for the silver nanoparticles. The nanoparticles obtained was characterized using UV, FTIR and SEM analysis. Results: A colour change from light yellow solution to reddish brown indicated silver reduction. UV-Vis spectrum of reaction medium displayed an emission peak at 320.5nm, which corresponded to the absorbance of silver nanoparticles and showed well dispersed nanoparticles in the aqueous solution without aggregation in UV-Vis absorption spectrum. The particle size of the resultant nanoparticles was 70.37 nm. Conclusion: Omeprazole silver-loaded nanoparticles was successfully formulated using green method.